2007
DOI: 10.1105/tpc.106.048447
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Flowering inArabidopsisRequires Activation ofFLOWERING LOCUS CExpression by the Histone Variant H2A.Z

Abstract: The histone variant H2A.Z has been implicated in numerous chromatin-mediated processes, including transcriptional activation, euchromatin maintenance, and heterochromatin formation. In yeast and humans, H2A.Z is deposited into chromatin by a conserved protein complex known as SWR1 and SRCAP, respectively. Here, we show that mutations in the Arabidopsis thaliana homologs of two components of this complex, ACTIN-RELATED PROTEIN6 (ARP6) and PHOTO-PERIOD-INDEPENDENT EARLY FLOWERING1 (PIE1), produce similar develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
352
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(404 citation statements)
references
References 46 publications
33
352
1
6
Order By: Relevance
“…These subunits interact with three Arabidopsis homologs of H2A.Z proteins, HTA8, HTA9, and HTA11 (Choi et al, 2007), indicating that the SWR1 complex is involved in H2A.Z deposition. The loss-of-function pie1 mutant flowers early because PIE1 is required for the deposition of H2A.Z at FLC, MAF4, and MAF5 (Deal et al, 2007). NuA4, the only essential histone acetyltransferase complex in S. cerevisiae, acetylates the N-terminal tails of histones H4 and H2A, which directly stimulates the incorporation of H2A.Z by the SWR1 complex (Altaf et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These subunits interact with three Arabidopsis homologs of H2A.Z proteins, HTA8, HTA9, and HTA11 (Choi et al, 2007), indicating that the SWR1 complex is involved in H2A.Z deposition. The loss-of-function pie1 mutant flowers early because PIE1 is required for the deposition of H2A.Z at FLC, MAF4, and MAF5 (Deal et al, 2007). NuA4, the only essential histone acetyltransferase complex in S. cerevisiae, acetylates the N-terminal tails of histones H4 and H2A, which directly stimulates the incorporation of H2A.Z by the SWR1 complex (Altaf et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether this global increase was due to an enhanced expression of H2A.Z variants, quantitative analysis of the expression of genes encoding H2A.Z was performed. The Arabidopsis genome encodes 13 H2A histones, 3 of which are H2A.Z variants (Deal et al, 2007). Quantitative PCR showed that in Arabidopsis, H2A.Z mRNA was mainly transcribed from the HTA9 gene (Supplemental Figure 6) and that no increase in the expression of this gene was detected in BAF60 RNAi lines, suggesting that H2A.Z accumulation is regulated at the protein level.…”
Section: H2az Deposition and Chromatin Condensation Are Impaired Inmentioning
confidence: 99%
“…Among genes known to be regulated via H2A.Z incorporation into chromatin, several are involved in the control of flowering time (Deal et al, 2007;Farrona et al, 2011). Hence, we compared the flowering time of BAF60 RNAi lines and Wassilewskija control plants in two independent experiments.…”
Section: Baf60 Influences Flowering Time and Co Ft Soc1 And Flc Exmentioning
confidence: 99%
See 1 more Smart Citation
“…The full activation of FLC by FRI requires chromatin modifiers, including proteins catalyzing histone H2B ubiquitination/deubiquitination, histone H3 lysine 4 (H3K4) methylation, H3K36 methylation, and the PAF1 (RNA polymerase associated factor 1) complex (Kim et al, 2009). In addition, the orthologous components of the yeast ATP-dependent SWR1 chromatin remodeling complex (SWR1-C), such as PHOTOPERIOD INDEPENDENT EARLY FLOWERING1 (PIE1), ACTIN-RELATED PROTEIN6 (ARP6)/SUPPRESSOR OF FRIGIDA3 (SUF3), and SWC6, are also required for incorporation of H2A.Z into FLC chromatin (Noh and Amasino, 2003;Choi et al, 2007;Deal et al, 2007). These chromatin-modifying proteins are well conserved among eukaryotes and are required for the epigenetic marks that are used for active transcription (Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%